Effects of dietary supplementation of Aspergillus originated prebiotic (Fermacto) on performance and small intestinal morphology of broiler chickens fed diluted diets - Zarbakht Ansari Pirsaraei; Masoud Adibmoradi; Bahman Navidshad (Italian Journal of Animal Science, 2010)
Fermacto, that it is commercially a fermentation product of Aspergillus orizae, is proven to increase digestion efficiency of the gut. In this experiment, 450 one day old Cobb 500 broiler chicks (mixed-sex) were used in a completely randomized design with 3×2 factorial arrangement. There were three levels of Fermacto (0, 0.15 and 0.3% for 42 days) and two levels of diet dilution using rice hulls (0 and 40% at 10-21 days of age). The treatments consisted of 3 replicates with 25 chicks per each. Administration of Fermacto did not influence feed intake or feed conversion ratio, but the daily weight gain improved. Diluted diets significantly increased body weights and decreased feed intake; however, this manipulation didn’t affect feed conversion ratios. There was no interaction between prebiotic supplementation and experimental diets dilution for performance traits. Diet dilution significantly decreased abdominal fat pad, villi height and increased epithelial thickness and goblet cell numbers. Dietary supplementation using Fermacto significantly decreased the abdominal fat pad and goblet cell numbers but increased the small intestinal villus heights. There were some conflicting observations for different segments of the small intestine. The 0.3% Fermacto inclusion in experimental diets caused more beneficial effects. Contrary to previous reports on more efficiency of Fermacto on low protein diets, this trend is not seen for the whole diluted diets.